2018
DOI: 10.1002/wsb.868
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying damage from wild pigs with small unmanned aerial systems

Abstract: Wild pig (Sus scrofa) population expansion and associated damage to crops, wildlife, and the environment is a growing concern in the United States. The destructive rooting behavior of wild pigs indicates where they have foraged and their general presence on the landscape. We used aerial imagery with a small unmanned aerial system to assess damage of corn (Zea mays) fields by wild pigs in the Mississippi Alluvial Valley of Mississippi, USA, during the 2016 growing season. Images were automatically classified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Estimates of area damaged by wild pigs (0.005-0.2 ha) were similar to estimates in Mississippi using UAS and segmentation-based fractal texture analysis (Samiappan et al, 2018), but considerably less than estimates in northern Belgium using UAS and geographic object-based image analysis (Rutten et al, 2018). This may be the result of wild pig elimination programs occurring across Missouri and much the U.S., which has presumably lowered wild pig densities (Centner and Shuman, 2015;U.S.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Estimates of area damaged by wild pigs (0.005-0.2 ha) were similar to estimates in Mississippi using UAS and segmentation-based fractal texture analysis (Samiappan et al, 2018), but considerably less than estimates in northern Belgium using UAS and geographic object-based image analysis (Rutten et al, 2018). This may be the result of wild pig elimination programs occurring across Missouri and much the U.S., which has presumably lowered wild pig densities (Centner and Shuman, 2015;U.S.…”
Section: Discussionmentioning
confidence: 56%
“…Although inaccuracies in classification maps and estimated damage areas will exist for any UAS-based approach, we consider our method to be an objective, time-efficient, and accurate approach. Past studies, using visible or crop height information, have indicated that UAS-based imagery approaches underestimate damage caused by wild pigs (Michez et al, 2016;Samiappan et al, 2018). Some of this error was due to ortho-mosaic and classification procedures, while other error was due to alignment errors of ground reference data and damage maps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent proliferation and expansion of wild pigs is credited to both behavioral and anthropogenic factors (Seward et al 2004, Bevins et al 2014, Tabak et al 2017). Wild pigs are highly adaptable, have an omnivorous diet, and high reproductive rates (Singer et al 1984, Samiappan et al 2018). Besides dispersing on their own, humans also translocate and release wild pigs due to their popularity with hunters (Seward et al 2004, Bevins et al 2014, Tabak et al 2017, McCann et al 2018, Fischer et al 2020).…”
mentioning
confidence: 99%